Becoming working mothers: reconciling work and family at three particular workplaces in Norway, the UK, and Portugal - Sümer, S.; Smithson, J.; Guerreiro, M. D.; Granlund, L. (Community, Work and Family, 2008)
This paper investigates how differences in national and organisational welfare policies and in cultural norms on national, organisational, and familial levels influence work–family reconciliation for mothers. Drawing on case study and interview data gathered through a large European study of parenthood and organisations, we compare experiences of transition to motherhood in three organisations in Norway, the UK, and Portugal. The specific question which is considered in this paper is how mothers manage the reconciliation of work and family in the period of time following parental leave. Our case analyses highlight the differences in organisational, national policy, and family support in the three contexts, and show that having a child is still conceptualised as a predominantly ‘private problem’ in the UK and Portugal, while it has come closer to having the status of a ‘public issue’ in Norway.